Fractalkine Signaling Regulates Macrophage Recruitment into the Cochlea and Promotes the Survival of Spiral Ganglion Neurons after Selective Hair Cell Lesion - Kaur, Tejbeer (J Neurosci, 2015)
Macrophages are recruited into the cochlea in response to injury caused by acoustic trauma or ototoxicity, but the nature of the interaction between macrophages and the sensory structures of the inner ear remains unclear. The present study examined the role of fractalkine signaling in regulating the injury-evoked behavior of macrophages following the selective ablation of cochlear hair cells. We used a novel transgenic mouse model in which the human diphtheria toxin receptor (huDTR) is selectively expressed under the control of Pou4f3, a hair cell-specific transcription factor. Administration of diphtheria toxin (DT) to these mice resulted in nearly complete ablation of cochlear hair cells, with no evident pathology among supporting cells, spiral ganglion neurons, or cells of the cochlear lateral wall. Hair cell death led to an increase in macrophages associated with the sensory epithelium of the cochlea. Their numbers peaked at 14 days after DT and then declined at later survival times. Increased macrophages were also observed within the spiral ganglion, but their numbers remained elevated for (at least) 56 d after DT. To investigate the role of fractalkine signaling in macrophage recruitment, we crossed huDTR mice to a mouse line that lacks expression of the fractalkine receptor (CX(3)CR1). Disruption of fractalkine signaling reduced macrophage recruitment into both the sensory epithelium and spiral ganglion and also resulted in diminished survival of spiral ganglion neurons after hair cell death. Our results suggest a fractalkine-mediated interaction between macrophages and the neurons of the cochlea. SIGNIFICANCE STATEMENT It is known that damage to the inner ear leads to recruitment of inflammatory cells (macrophages), but the chemical signals that initiate this recruitment and the functions of macrophages in the damaged ear are unclear. Here we show that fractalkine signaling regulates macrophage recruitment into the cochlea and also promotes the survival of cochlear afferents after selective hair cell lesion. Because these afferent neurons carry sound information from the cochlea to the auditory brainstem, their survival is a key determinant of the success of cochlear prosthetics. Our data suggest that fractalkine signaling in the cochlea is neuroprotective, and reveal a previously uncharacterized interaction between cells of the cochlea and the innate immune system.